2016
DOI: 10.1371/journal.pone.0151807
|View full text |Cite
|
Sign up to set email alerts
|

High Prevalence of Post-Traumatic Stress Symptoms in Relation to Social Factors in Affected Population One Year after the Fukushima Nuclear Disaster

Abstract: ObjectiveThis study investigated post-traumatic stress symptoms in relation to the population affected by the Fukushima Nuclear Disaster, one year after the disaster. Additionally, we investigated social factors, such as forced displacement, which we hypothesize contributed to the high prevalence of post-traumatic stress. Finally, we report of written narratives that were collected from the impacted population.Design and SettingsUsing the Impact of Event Scale-Revised (IES-R), questionnaires were sent to 2,011… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
39
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(45 citation statements)
references
References 31 publications
4
39
0
2
Order By: Relevance
“…8 It may begin within the first six months after the event [although not necessarily, since the 10 Studies on PTSD have been carried out with war veterans, survivors of disasters and natural catastrophes, sexual abuse victims, among many other situations that present an imminent risk of death. 10,11 There are, however, few findings related the occurrence of this disorder in HCWs exposed to PCBM, 3,6 which motivated this investigation.…”
Section: -5mentioning
confidence: 96%
“…8 It may begin within the first six months after the event [although not necessarily, since the 10 Studies on PTSD have been carried out with war veterans, survivors of disasters and natural catastrophes, sexual abuse victims, among many other situations that present an imminent risk of death. 10,11 There are, however, few findings related the occurrence of this disorder in HCWs exposed to PCBM, 3,6 which motivated this investigation.…”
Section: -5mentioning
confidence: 96%
“…Historic inequities driving chronic disease rates in people of color, poverty, and health literacy may play a role in differential rates of infection and death. Individuals whose livelihood and ability to obtain food and shelter have been diminished may suffer long‐term consequences of this pandemic 4 , and those with pre‐existing mental health disorders may be at increased risk for developing post‐traumatic stress disorder or suicidal ideation 5,6 .…”
mentioning
confidence: 99%
“…Consistent with the study of Husky et al 35 , which emphasized the burden of comorbid medical conditions in PTSD, we also observed in our study that PTSD is associated with a significantly higher probability of chronic diseases. Tsujiuchi et al 41 reported that significant predictors of probable PTSD were chronic physical diseases such as hypertension, hyperlipidemia, obesity, and coronary heart disease. Previous research in the general population found that PTSD respondents were 3 times more likely to report a family history of mental illness 42 , in contrast, in another study, patients with PTSD did not differ from nonpsychiatric controls on the basis of family history 43 .…”
Section: Discussionmentioning
confidence: 99%